Thermodynamic description of Tc(iv) solubility and carbonate complexation in alkaline NaHCO3–Na2CO3–NaCl systems. Issue 12 (2nd March 2018) - Baumann, A.; Yalçıntaş, E.; Gaona, X.; Polly, R.; Dardenne, K.; Prüßmann, T.; Rothe, J.; Altmaier, M.; Geckeis, H.
Abstract : A comprehensive thermodynamic model is derived for the system Tc 4+ –Na + –Cl − –OH − –HCO3 − –CO3 2− –H2 O(l) based upon solubility experiments in alkaline carbonate solutions, advanced spectroscopic techniques and DFT calculations. Abstract : The solubility of 99 Tc(iv ) was investigated in dilute to concentrated carbonate solutions (0.01 M ≤ Ctot ≤ 1.0 M, with Ctot = [HCO3 − ] + [CO3 2− ]) under systematic variation of ionic strength ( I = 0.3–5.0 M NaHCO3 –Na2 CO3 –NaCl–NaOH) and pHm (−log[H + ] = 8.5–14.5). Strongly reducing conditions (pe + pHm ≈ 2) were set with Sn(ii ). Carbonate enhances the solubility of Tc(iv ) in alkaline conditions by up to 3.5 log10 -units compared to carbonate-free systems. Solvent extraction and XANES confirmed that Tc was kept as +IV during the timeframe of the experiments (≤ 650 days). Solid phase characterization performed by XAFS, XRD, SEM-EDS, chemical analysis and TG-DTA confirmed that TcO2 ·0.6H2 O(am) controls the solubility of Tc(iv ) under the conditions investigated. Slope analysis of the solubility data in combination with solid/aqueous phase characterization and DFT calculations indicate the predominance of the species Tc(OH)3 CO3 − at pHm ≤ 11 and Ctot ≥ 0.01 M, for which thermodynamic and activity models are derived. Solubility data obtained above pHm ≈ 11 indicates the formation of previously unreported Tc(iv )–carbonate species, possibly Tc(OH)4 CO3 2−, although the likely formation of additional complexes prevents deriving a thermodynamic model valid for this pHm -region. This work provides the most comprehensive thermodynamic dataset available for the system Tc 4+ –Na + –Cl − –OH − –HCO3 − –CO3 2− –H2 O(l) valid under a range of conditions relevant for nuclear waste disposal.